Parallel Reduction of Plasma Levels of High and Low Molecular Weight Kininogen in Patients with Cirrhosis - Cugno, Massimo; Scott, Cheryl F.; Salerno, Francesco; Lorenzano, Elettra; Müller-Esterl, Werner; Agostoni, Angelo; Colman, Robert W. (Thrombosis and Haemostasis, 1999)
Little is known about the regulation of high-molecular-weight-kininogen (HK) and low-molecular-weight-kininogen (LK) or the relationship of each to the degree of liver function impairment in patients with cirrhosis. In this study, we evaluated HK and LK quantitatively by a recently described particle concentration fluorescence immunoassay (PCFIA) and qualitatively by SDS PAGE and immunoblotting analyses in plasma from 33 patients with cirrhosis presenting various degrees of impairment of liver function. Thirty-three healthy subjects served as normal controls. Patients with cirrhosis had significantly lower plasma levels of HK (median 49 μg/ml [range 22-99 μg/ml]) and LK (58 μg/ml [15-100 μg/ml]) than normal subjects (HK 83 μg/ml [65-115 μg/ml]; LK 80 μg/ml [45-120 μg/ml]) (p < 0.0001). The plasma concentrations of HK and LK were directly related to plasma levels of cholinesterase (P < 0.0001) and albumin (P < 0.0001 and P < 0.001) and inversely to the Child-Pugh score (P < 0.0001) and to prothrombin time ratio (P < 0.0001) (reflecting the clinical and laboratory abnormalities in liver disease). Similar to normal individuals, in patients with cirrhosis, plasma HK and LK levels paralleled one another, suggesting that a coordinate regulation of those proteins persists in liver disease. SDS PAGE and immunoblotting analyses of kininogens in cirrhotic plasma showed a pattern similar to that observed in normal controls for LK (a single band at 66 kDa) with some lower molecular weight forms noted in cirrhotic plasma. A slight increase of cleavage of HK (a major band at 130 kDa and a faint but increased band at 107 kDa) was evident. The increased cleavage of HK was confirmed by the lower cleaved kininogen index (CKI), as compared to normal controls. These data suggest a defect in hepatic synthesis as well as increased destructive cleavage of both kininogens in plasma from patients with cirrhosis. The decrease of important regulatory proteins like kininogens may contribute to the imbalance in coagulation and fibrinolytic systems, which frequently occurs in cirrhotic patients.
Keywords: High molecular weight kininogen; low molecular weight kininogen; liver cirrhosis